Evidence to Action: Highlights From Transform Nutrition Research (2012-2017). Issue 3 (September 2018) - Gillespie, Stuart; Hoddinott, John; Nisbett, Nicholas; Arifeen, Shams; van den Bold, Mara
Background: The Transform Nutrition ( Transform ) research consortium (2012-2017), led by the International Food Policy Research Institute, sought to generate evidence to inform and inspire action to address undernutrition in 4 high-burden countries (India, Bangladesh, Kenya, and Ethiopia) and globally. Objective: Within the context of the literature, this synthesis article brings together core findings of Transform, highlighting priorities for future research. Methods: This article uses a narrative approach to synthesize diverse study findings that collectively address Transform's three primary research questions: (1) How can nutrition-specific interventions be appropriately designed, implemented, scaled, and sustained in different settings?; (2) How can the nutritional impact of social protection and agriculture be improved?; and (3) How can enabling environments be promoted so as to use existing political and economic resources more effectively? Results: Highlights of Transform include (1) improved understanding of the relative effectiveness of different combinations of nutrition-specific interventions and the ways in which they can be scaled for maximal impact; (2) evidence that shows that social protection and agriculture need to be explicitly linked to nutrition in order to contribute to stunting reduction; (3) identification of key components of "enabling environments" for nutrition and how they can be cultivated/sustained; (4) research that examines ways in which leaders emerge and operate to change the political and policy landscape in different settings; and (5) "stories of change" that provide in-depth contextual knowledge of how transformative change has been driven in countries that have made inroads in reducing malnutrition. The conclusion highlights the contributions of the consortium and provides recommendations for future research.